THE RISE OF DIGITAL INVESTMENTS: OPPORTUNITIES AND CHALLENGES - Mukhitdinova Kamola Alisherovna (Ecominds Press, 2025)
Digital investments have transformed the global financial landscape by offering greater access, efficiency, and transparency in asset management. This paper explores the various forms of digital investments, including cryptocurrencies, robo-advisors, digital real estate platforms, and tokenized assets. It also examines the benefits, risks, and regulatory challenges associated with these innovations.
Keywords: Digital Investments, Cryptocurrency, Robo-Advisors, Blockchain, FinTech, Tokenization.